Diagnosis and surgical management strategy for pediatric small bowel obstruction: Experience from a single medical center - Liu, Mingzhu; Cheng, Fengchun; Liu, Xijie; Zheng, Bufeng; Wang, Feifei; Qin, Chengwei; Ding, Guojian; Fu, Tingliang; Geng, Lei (Frontiers in Surgery, 2023)
Identifying Bowel strangulation and the approach and timing of surgical intervention for pediatric SBO are still uncertain. In this study, 75 consecutive pediatric patients with surgically confirmed SBO were retrospectively reviewed. The patients were divided into group 1 (n = 48) and group 2 (n = 27) according to the presence of reversible or irreversible bowel ischemia, which was analyzed based on the degree of ischemia at the time of operation. The results demonstrated that the proportion of patients with no prior abdominopelvic surgery was higher, the serum albumin level was lower, and the proportion of patients in which ascites were detected by ultrasonography was higher in group 2 than that in group 1. The serum albumin level was negatively correlated with ultrasonographic findings of the fluid sonolucent area in group 2. There were significant differences in the choice of surgical approach between group 1 and group 2. A symptom duration of >48 h was associated with an increased bowel resection rate. The mean length of hospital stay was shorter in group 1 than that in group 2. In conclusion, immediate surgical intervention should be considered in patients with a symptom duration of >48 h or the presence of free ascites between dilated small bowel loops on ultrasonography. Laparoscopic exploration is recommended as first-line treatment in patients with stable status.